Plany rozwoju społeczno-gospodarczego na szczeblu gminy - Dąbrowski, Zdzisław (Wydział Prawa i Administracji UAM, 1979)
The article is devoted mainly to showing the place and role of plans of communes — introduced at the beginning of 1973 — in general system of national plans of socio-economic development. On the background of three basic functions of a commune plan, i.e. decisive-obligatory, coordinative-integrating and informative-organizational functions, its specific character has been presented. This character determines a mechanism of generation, functioning and realization of the plan. According to central regulations, a plan of a commune is elaborated on the ground of general principles (resolutions of the commune's people's council and tabular specifications) and it is characterized by rather schematic contents while adaptation of plan contents to socio-economic characteristics and to the most important commune problems is indispensable. There is also the necessity pointed out in the article of renouncing the until now practice in which the problem-contents formulation of a five-year commune plan is shaped according to the scope pattern and contents detailed structure of a one-year plan. The present influence of plans of central and voivodeship levels on commune plans should be then supplemented by a broader reverse influence of commune plans on plan regulations of higher levels, taking on simultaneously a more essential character, creating thus a real practice of planning.
Plans of Socio-Economic Development at the Commune Level